Olelo: a web application for intuitive exploration of biomedical literature. Issue Volume 45:Issue W1(2017) (3rd May 2017) - Kraus, Milena; Niedermeier, Julian; Jankrift, Marcel; Tietböhl, Sören; Stachewicz, Toni; Folkerts, Hendrik; Uflacker, Matthias; Neves, Mariana
Abstract: Researchers usually query the large biomedical literature in PubMed via keywords, logical operators and filters, none of which is very intuitive. Question answering systems are an alternative to keyword searches. They allow questions in natural language as input and results reflect the given type of question, such as short answers and summaries. Few of those systems are available online but they experience drawbacks in terms of long response times and they support a limited amount of question and result types. Additionally, user interfaces are usually restricted to only displaying the retrieved information. For our Olelo web application, we combined biomedical literature and terminologies in a fast in-memory database to enable real-time responses to researchers' queries. Further, we extended the built-in natural language processing features of the database with question answering and summarization procedures. Combined with a new explorative approach of document filtering and a clean user interface, Olelo enables a fast and intelligent search through the ever-growing biomedical literature. Olelo is available at http://www.hpi.de/plattner/olelo .